2021
DOI: 10.1016/j.jcmgh.2021.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Nonalcoholic Steatohepatitis and HCC in a Hyperphagic Mouse Accelerated by Western Diet

Abstract: This study establishes a relevant mouse model of nonalcoholic steatohepatitis-fibrosis-hepatocellular carcinoma that closely recapitulates human disease. With this model, we elucidate multitissue dynamics of nonalcoholic steatohepatitis/hepatocellular carcinoma progression, as well as regression. We define the key signaling and cytokine pathways that are critical for disease development and resolution.BACKGROUND & AIMS: How benign liver steatosis progresses to nonalcoholic steatohepatitis (NASH), fibrosis, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 61 publications
(86 reference statements)
1
18
0
Order By: Relevance
“…Ultimately, it has been recently demonstrated that mice carrying a loss-of-function mutation in the Alms1 gene, also known as Foz / Foz mice, display hyperphagia and multiple aspects of metabolic syndrome, among which obesity, IR, dyslipidemia and hypertension [ 223 , 224 ]. In addition, when Foz / Foz mice are fed with a WD rapidly develop NASH in 4 weeks and advanced fibrosis in 12 weeks of diet, mimicking human pathobiology.…”
Section: Preclinical Models To Induce Nash-hcc: From Dietary Supplementation To Geneticsmentioning
confidence: 99%
“…Ultimately, it has been recently demonstrated that mice carrying a loss-of-function mutation in the Alms1 gene, also known as Foz / Foz mice, display hyperphagia and multiple aspects of metabolic syndrome, among which obesity, IR, dyslipidemia and hypertension [ 223 , 224 ]. In addition, when Foz / Foz mice are fed with a WD rapidly develop NASH in 4 weeks and advanced fibrosis in 12 weeks of diet, mimicking human pathobiology.…”
Section: Preclinical Models To Induce Nash-hcc: From Dietary Supplementation To Geneticsmentioning
confidence: 99%
“… 4 Foz / Foz mice fed high-calorie diets have been used previously to model NASH in a couple of studies. In the present report, however, Ganguly et al 3 selected a Western diet and performed a comprehensive characterization of the model. Strikingly, Foz / Foz mice on the Western diet developed severe obesity and histologic features of NASH within 4 weeks of feeding, and NASH with grade 3 fibrosis after 12 weeks on the diet.…”
mentioning
confidence: 92%
“…Conversely, Western diet–fed Foz / Foz mice resemble human disease etiology and develop NASH-HCC in a reasonable time frame for preclinical research. An aspect not reported in the study by Ganguly et al 3 but worth further exploration is the in-depth molecular characterization of HCC tumors in Western diet–fed Foz / Foz mice. Future studies are necessary to comprehend the transcriptomic and mutational landscape of this murine HCC in comparison with human NASH-induced HCC, which will be the ultimate test of human pathophysiological relevance.…”
mentioning
confidence: 95%
See 2 more Smart Citations